An impedance spectroscopy study in poly(butylene adipate) ionomers - Yakuphanoğlu, Fahrettin; Yoo, YT; Okutan, M (Wiley-V C H Verlag Gmbh, 2004)
Poly(butylenes adipate) ionomers (PBAi) were synthesized using dimethyl 5-sulfoisophthalate sodium salt (DMSI) up to 5 mol% of diacid monomer. We have investigated electrical and dielectric properties of the ionomers to evaluate alternating current (AC) parameters such as impedance, conductance, dielectric constant, admittance, susceptance, dielectric loss, and resistance by an impedance spectroscopy. It is seen that the ionic conductances of the ionomers increase with increasing content of DMSI. The AC conductance for the ionomers was found to vary as omega(s) with the index s greater than or equal to 1. A decrease in the relative dielectric constant of the ionomers is observed with the increase in the ionic content. The electrical relaxation in the dielectric spectra of the ionomers was not observed due to the orientation polarization of the dipoles. It is also observed that the tangent loss increases with the increase in the ionic content. (C) 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: ionomer; dielectric loss and relaxation; permittivity; dielectric function